Determination of μ-, δ- and κ-opioid receptors in forebrain cortex of rats exposed to morphine for 10 days: Comparison with animals after 20 days of morphine withdrawal - Ujcikova, Hana; Hlouskova, Martina; Cechova, Kristina; Stolarova, Katerina; Roubalova, Lenka; Svoboda, Petr (PloS one, 2017)
BACKGROUND: Chronic exposure of mammalian organism to morphine results in adaption to persistent high opioid tone through homeostatic adjustments. Our previous results indicated that in the frontal brain cortex (FBC) of rats exposed to morphine for 10 days, such a compensatory adjustment was detected as large up-regulation of adenylylcyclases I (8-fold) and II (2.5-fold). The other isoforms of AC (III-IX) were unchanged. Importantly, the increase of ACI and ACII was reversible as it disappeared after 20 days of morphine withdrawal. Changes of down-stream signaling molecules such as G proteins and adenylylcyclases should respond to and be preceded by primary changes proceeding at receptor level. Therefore in our present work, we addressed the problem of reversibility of the long-term morphine effects on μ-, δ- and κ-OR protein levels in FBC. METHODS: Rats were exposed to increasing doses of morphine (10-40 mg/kg) for 10 days and sacrificed either 24 h (group +M10) or 20 days (group +M10/-M20) after the last dose of morphine in parallel with control animals (groups -M10 and -M10/-M20). Post-nuclear supernatant (PNS) fraction was prepared from forebrain cortex, resolved by 1D-SDS-PAGE under non-dissociated (-DTT) and dissociated (+DTT) conditions, and analyzed for the content of μ-, δ- and κ-OR by immunoblotting with C- and N-terminus oriented antibodies. RESULTS: Significant down-regulation of δ-OR form exhibiting Mw ≈ 60 kDa was detected in PNS prepared from both (+M10) and (+M10/-M20) rats. However, the total immunoblot signals of μ-, δ- and κ-OR, respectively, were unchanged. Plasma membrane marker Na, K-ATPase, actin and GAPDH were unaffected by morphine in both types of PNS. Membrane-domain marker caveolin-1 and cholesterol level increased in (+M10) rats and this increase was reversed back to control level in (+M10/-M20) rats. CONCLUSIONS: In FBC, prolonged exposure of rats to morphine results in minor (δ-OR) or no change (μ- and κ-OR) of opioid receptor content. The reversible increases of caveolin-1 and cholesterol levels suggest participation of membrane domains in compensatory responses during opioid withdrawal. GENERAL SIGNIFICANCE: Analysis of reversibility of morphine effect on mammalian brain.
Keywords: receptory opiátové delta; Electrophoresis, Polyacrylamide Gel; Prosencephalon; Receptors, Opioid, delta; Receptors, Opioid, mu; receptory opiátové kappa; 2D gelová elektroforéza; elektroforéza v polyakrylamidovém gelu; přední mozek; abstinenční syndrom; Blotting, Western; Morphine; krysa rodu Rattus; zvířata; potkani Wistar; Rats, Wistar; Male; Receptors, Opioid, kappa; Electrophoresis, Gel, Two-Dimensional; Rats; receptory opiátové mu; morfin; Animals; western blotting; mužské pohlaví; Substance Withdrawal Syndrome